1998
DOI: 10.1007/pl00005219
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory and inhibitory effects of ethanol on hippocampal acetylcholine release

Abstract: Using the microdialysis technique and sensitive HPLC procedures for the determination of acetylcholine (ACh) and ethanol, we investigated the release of ACh in rat hippocampus after acute ethanol administration. Systemic administration of ethanol (0.8 and 2.4 g/kg i.p.) led to peak ethanol concentrations of 21 and 42 mM in the hippocampus, respectively. The high dose caused a long-lasting inhibition of basal ACh release by up to 33%. Local infusion of scopolamine (1 microM) enhanced hippocampal ACh release up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…In a rat model, a moderate concentration of ethanol (0.8 g/kg) stimulated the release of acetylcholine while a higher concentration (2.4 g/kg) inhibited its release [115]. The formation of amyloid fibrillar plaques is also common in diseases such as Parkinson's disease, prion diseases, Down's syndrome and type II diabetes [116][117][118][119][120][121].…”
Section: Neurotransmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a rat model, a moderate concentration of ethanol (0.8 g/kg) stimulated the release of acetylcholine while a higher concentration (2.4 g/kg) inhibited its release [115]. The formation of amyloid fibrillar plaques is also common in diseases such as Parkinson's disease, prion diseases, Down's syndrome and type II diabetes [116][117][118][119][120][121].…”
Section: Neurotransmissionmentioning
confidence: 99%
“…Alcohol acts directly and indirectly on the central nervous system [14,16,115] and alcohol abuse causes cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…The present results also show that, the pretrain and pre-test administration of ethanol also reversed the decrease in inhibitory avoidance response induced by ethanol. Studies suggested that the inhibition of hippocampal ACh release by intoxicating doses of ethanol may contribute to the wellknown cognitive and amnesic effects of ethanol intake [29]. Acute ethanol administration produces dose-dependent impairments in spatial learning.…”
Section: Discussionmentioning
confidence: 99%
“…175 In a rat model, a moderate concentration of alcohol (0.8 g/kg) stimulated the release of acetylcholine while a higher concentration (2.4 g/kg) inhibited its release. 176 Four studies have further suggested that moderate wine consumption is associated with a lower risk of dementia and specifically Alzheimer's disease. [176][177][178][179][180][181] In the prospective population-based study by Orgogozo and colleagues 176 the sole source of alcohol was wine for 95% of consumers, which did not allow for beverage differentiation.…”
Section: Effect Of Wine On Alzheimer's Disease and Dementiamentioning
confidence: 99%
“…176 Four studies have further suggested that moderate wine consumption is associated with a lower risk of dementia and specifically Alzheimer's disease. [176][177][178][179][180][181] In the prospective population-based study by Orgogozo and colleagues 176 the sole source of alcohol was wine for 95% of consumers, which did not allow for beverage differentiation. In the Copenhagen City Heart Study (1991−1994) and in the Washington Heights InwoodColumbia Aging Project (1991−1996), however, only wine was associated with a lower risk or incidence.…”
Section: Effect Of Wine On Alzheimer's Disease and Dementiamentioning
confidence: 99%